Effects of species and moisture content on the behaviour of solid wood under impact - Hassan Vand, Mojtaba; Tippner, Jan; Brabec, Martin (Springer New York, 2024)
The article's main aim is to assess the effects of species and moisture content (MC) on the behaviour of solid wood material under the low velocity of impact and present a pattern for predicting loading vs time curves for these species in different moisture levels. Three groups of samples (300 x 20 x 20 mm) were made from beech, oak, and spruce wood. Each group was subdivided into two groups with low moisture content (LMC) level (10-12%) and high moisture content (HMC) level (40-60%). A drop-weight impact machine did the tests, and high-speed cameras recorded the lateral specimens' surface during the impact. The digital image correlation technique (DIC) determined the strain pattern and the deflection. The timing of the crack initiation was also observed. Also, the force-time charts, the maximum force required for crack initiation, the work needed for crack initiation, and the total work required for the breakage of every specimen were gathered. A general force-time pattern with five identifiable steps was determined for each group. It turned out that the maximum deflection and longitudinal tensile strain of the beams up to crack initiation increase with increased moisture content while maximum force decreases. Unlike beech, the required work for rupture of HMC samples of oak and spruce is higher than LMC group.
Keywords: digital image correlation; temperature; toughness; spruce